Service Quality Dimensions (SERVQUAL) and Customer Satisfaction towards Motor Ride-Sharing Services: Evidence from Bangladesh - Sharmila Sikder; Md. Masud Rana; Mohammad Rashed Hasan Polas (goodwood publishing, 2021)
Purpose: This study aimed to examine and evaluate the factors affecting Bangladeshi ride-sharing consumers' satisfaction levels. Research methodology: The samples comprised 386 users of this application in Dhaka city selected using a convenience random sampling technique. The data obtained using a survey questionnaire were evaluated using Smart PLS 3.0. Furthermore, six hypotheses were developed to realize the objectives. This study used a positivist research methodology. Results: The results showed a positive and significant relationship between tangibility, responsiveness, empathy, price fairness, and customer satisfaction. There is no conventional relationship between reliability and assurance of customer satisfaction. Limitations: Customer satisfaction is vast, and this study only examined ride-sharing services in Dhaka city using SERVQUAL dimensions, which restricts the generalizability of the results. Contribution: The findings would help the service providers participating in this operation better understand the appropriate actions to improve their commuter services.